STUDI KASUS : ASUHAN KEBIDANAN PADA Ny.W MASA KEHAMILAN TRIMESTER III, PERSALINAN, NIFAS, NEONATUS DAN KELUARGA BERENCANA: CASE STUDY: MIDWIFE CARE ON MY WHILE TRIMESTER III PREGNANCY, LABOR, NIFAS, NEONATUS AND FAMILY PLANNING - Nafisatul Khoiriah Rapi; Septi Tri Aksari; Ellyzabeth Sukmawati; Yuli Sya’baniah; Norif Didik Nur Imanah (Lembaga Pengembangan Kinerja Dosen, 2022)
During the Covid-19 pandemic, there was a decrease in the coverage of pregnancy services compared to the previous year. Especially during a pandemic like this sometimes pregnant women don't want to check themselves and their wombs for fear of being exposed to the Covid-19 virus. Continuity of Care (COC) or comprehensive midwifery care is a sustainable midwifery service and is one way to reduce MMR and IMR, especially those that occur at the Maos Health Center by providing care for pregnant women in the third trimester, childbirth, postpartum, neonates and family planning, at the Maos Health Center. With the provision of comprehensive midwifery care, it is hoped that every pregnant woman will get quality maternal health services so that mothers and babies remain healthy and can reduce maternal and infant mortality rates.